Epigenetic mechanisms and their significance in livestock species - Kanaka K K,; Sanjeev Singh,; Indrajit Ganguly,; Aishwarya Dash,; Nidhi Sukhja,; Nandhini P.B.,; S. P. Dixit, (Journal of Livestock Biodiversity, 2025)
Epigenetics refers to possible causal mechanisms acting on the genes that govern the phenotype. It plays a crucial role in many biological processes, such as gene imprinting, gene silencing, X chromosome inactivation, cell reprogramming etc. Epigenetic marks such as DNA methylation, histone tail modifications, chromatin remodelling, and other molecules which can transmit epigenetic information like noncoding RNA species constitute the “epigenome”. For years, animal selection in livestock species has been performed by selecting animals using genetic inheritance. However, genomic information alone explains only a section of the phenotypic variance in traits. It is likely that some of the unaccounted variance is embedded within the “epigenome”. Evolutionary studies have reported that non-genetic information derived from epigenetic, microbiota, environmental influences that drive natural selection can also be inherited across generations. Epigenetic factors respond to external or internal environmental factors like nutrition, microorganisms and climate have the ability to change gene expression leading to the emergence of specific phenotypes, which can be given consideration in livestock improvement programs. These diverse sources of inheritance can be utilized for the better prediction of the transmissable ability of the animal and thus can improve the methodologies of selection. Currently, high-throughput sequencing techniques and microarray-based techniques are intensively used in epigenomics profiling. The advances in next-generation sequencing technologies allow genome-wide profiling of methyl marks on DNA, which ultimately aims to find novel biomarkers for better understanding of complex polygenic traits. They can also be used along with genome-wide association study (GWAS), selection signature analysis and comparative epigenomics to shed light on potential adaptive evolution. However, epigenetic research on farm animal species is presently inadequate due to a lack of recognition, funding, and a worldwide integrated network of researchers.